\(\frac{5+\sqrt{5}}{\sqrt{5}+1}-\sqrt{6-2\sqrt{5}}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 6 2021

\(\frac{5+\sqrt{5}}{\sqrt{5}+1}-\sqrt{6-2\sqrt{5}}\)

\(=\sqrt{5}-\sqrt{\left(\sqrt{5}\right)^2-2\sqrt{5}+1}=\sqrt{5}-\sqrt{\left(\sqrt{5}-1\right)^2}\)

\(=\sqrt{5}-\left|\sqrt{5}-1\right|=\sqrt{5}-\sqrt{5}+1=1\)

26 tháng 7 2018

E = \(6x+\sqrt{9x^2-12x+4}\)

E = \(6x+\sqrt{\left(3x-2\right)^2}\)

E = \(6x+\left|3x-2\right|\)

E = \(6x+3x-2\)

E = \(9x-2\)

F = \(5x-\sqrt{x^2+4x+4}\)

F = \(5x-\sqrt{\left(x+2\right)^2}\)

F = \(5x-\left|x+2\right|\)

F = \(5x-x+2\)

F = \(4x+2\)

13 tháng 8 2020

P = \(\frac{2\sqrt{x}-9}{x-5\sqrt{x}+6}-\frac{\sqrt{x}+3}{\sqrt{x}-2}-\frac{2\sqrt{x}+1}{3-\sqrt{x}}\)

P = \(\frac{2\sqrt{x}-9-\left(\sqrt{x}+3\right)\left(\sqrt{x}-3\right)+\left(2\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)

P = \(\frac{2\sqrt{x}-9-x+9+2x-3\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)

P = \(\frac{x-\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)

P = \(\frac{x-2\sqrt{x}+\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)

P = \(\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)

P = \(\frac{\sqrt{x}+1}{\sqrt{x}-3}\)

Với \(x=6-2\sqrt{5}=5-2\sqrt{5}+1=\left(\sqrt{5}-1\right)^2\) 

=> P = \(\frac{\sqrt{\left(\sqrt{5}-1\right)^2}+1}{\sqrt{\left(\sqrt{5}-1\right)^2}-3}=\frac{\sqrt{5}-1+1}{\sqrt{5}-1-3}=\frac{\sqrt{5}}{\sqrt{5}-4}=\frac{\sqrt{5}\left(\sqrt{5}+4\right)}{\left(\sqrt{5}-4\right)\left(\sqrt{5}+4\right)}=\frac{5+4\sqrt{5}}{-11}\)

22 tháng 6 2017

=\(\sqrt{3-\sqrt{5}}\)\(\sqrt{2}\)(\(\sqrt{5}-1\)) (\(3+\sqrt{5}\))

=\(\sqrt{6-2\sqrt{5}}\)(\(\sqrt{5}-1\)) (\(3+\sqrt{5}\))

=\(\sqrt{\left(\sqrt{5}+1\right)^2}\)(\(\sqrt{5}-1\))(\(3+\sqrt{5}\))

=(\(\sqrt{5}+1\))(\(\sqrt{5}-1\))(\(3+\sqrt{5}\))

=4(\(3+\sqrt{5}\))

=12+4\(\sqrt{5}\)

5 tháng 8 2019

Đặt \(x=\sqrt[3]{\sqrt{5}+2}-\sqrt[3]{\sqrt{5}-2}.\)

\(\Rightarrow x^3=\sqrt{5}+2-3\sqrt[3]{\left(\sqrt{5}+2\right)\left(\sqrt{5}-2\right)}\left(\sqrt[3]{\sqrt{5}+2}-\sqrt[3]{\sqrt{5}-2}\right)-\sqrt{5}+2\)

         \(=4-3\sqrt[3]{5-4}.x\)( Vì \(x=\sqrt[3]{\sqrt{5}+2}-\sqrt[3]{\sqrt{5}-2}\))

        \(=4-3x\)

\(\Rightarrow x^3+3x-4=0\Leftrightarrow\left(x^3-1\right)+\left(3x-3\right)=0\)

\(\Leftrightarrow\left(x-1\right)\left(x^2+x+4\right)=0\Leftrightarrow x-1=0\)( Vì \(x^2+x+4=\left(x+\frac{1}{2}\right)^2+\frac{15}{4}>0\))

\(\Leftrightarrow x=1\)hay \(\sqrt[3]{\sqrt{5}+2}-\sqrt[3]{\sqrt{5}-2}=1\)

\(a,ĐKXĐ:a\ge0;a\ne4\)

\(P=\frac{\sqrt{a}+1}{\sqrt{a}-2}+\frac{2\sqrt{a}}{\sqrt{a}+2}-\frac{5\sqrt{a}+2}{a-4}\)

\(=\frac{\sqrt{a}+1}{\sqrt{a}-2}+\frac{2\sqrt{a}}{\sqrt{a}+2}-\frac{5\sqrt{a}+2}{\left(\sqrt{a}-2\right)\left(\sqrt{a}+2\right)}\)

\(=\frac{\left(\sqrt{a}+1\right)\left(\sqrt{a}+2\right)+2\sqrt{a}\left(\sqrt{a}-2\right)-5\sqrt{a}-2}{\left(\sqrt{a}-2\right)\left(\sqrt{a}+2\right)}\)

\(=\frac{a+3\sqrt{a}+2+2a-4\sqrt{a}-5\sqrt{a}-2}{\left(\sqrt{a}-2\right)\left(\sqrt{a}+2\right)}\)

\(=\frac{3a-6\sqrt{a}}{\left(\sqrt{a}-2\right)\left(\sqrt{a}+2\right)}\)

\(=\frac{3\sqrt{a}\left(\sqrt{a}-2\right)}{\left(\sqrt{a}-2\right)\left(\sqrt{a}+2\right)}=\frac{3\sqrt{a}}{\sqrt{a}+2}\)

\(b,P=2\Rightarrow\frac{3\sqrt{a}}{\sqrt{a}+2}=2\)

\(\Rightarrow3\sqrt{a}=2\left(\sqrt{a}+2\right)\)

\(\Rightarrow3\sqrt{a}=2\sqrt{a}+4\)

\(\Rightarrow3\sqrt{a}-2\sqrt{a}=4\)

\(\Rightarrow\sqrt{a}=4\)

\(\Rightarrow a=16\)

10 tháng 8 2021

Bài 1 : Với : \(x>0;x\ne1\)

\(P=\left(1+\frac{1}{\sqrt{x}-1}\right)\frac{1}{x-\sqrt{x}}=\left(\frac{\sqrt{x}}{\sqrt{x}-1}\right).\sqrt{x}\left(\sqrt{x}-1\right)=x\)

Thay vào ta được : \(P=x=25\)

10 tháng 8 2021

Bài 2 : 

a, Với \(x\ge0;x\ne1\)

\(A=\frac{\sqrt{x}}{\sqrt{x}-1}-\frac{2}{\sqrt{x}+1}-\frac{2}{x-1}=\frac{x+\sqrt{x}-2\sqrt{x}+2-2}{x-1}\)

\(=\frac{x-\sqrt{x}}{x-1}=\frac{\sqrt{x}\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}=\frac{\sqrt{x}}{\sqrt{x}+1}\)

Thay x = 9 vào A ta được : \(\frac{3}{3+1}=\frac{3}{4}\)